Developing a strategic action plan for reducing the burden of stroke in Africa: report of the first African Stroke Leaders' Summit - Akinyemi, Rufus; Olowoyo, Paul; Jones, Stephanie; Adeniji, Olaleye; Ogunde, Gabriel; Spencer, Joseph; Abd-Allah, Foad; Akpalu, Albert; Lightbody, Liz; Yaria, Joseph; Sarfo, Fred S.; Naidoo, Pamela; et al. (Frontiers in Stroke, 2025)
IntroductionStroke is a leading cause of adult neurologic disability, cognitive decline, and death worldwide, and particularly in Africa. Stroke research in Africa has exposed challenges militating against the translation of research evidence into practice and policy. The evidence-based, context-sensitive multilevel strategies required to surmount these challenges are presented in this report on the first African Stroke Leaders' Summit (ASLS) organized to tackle the burden of stroke in Africa.MethodsThe Africa–UK Stroke Partnership (AUKSP) Project had a Steering Committee (SC) and four theme-based Working Groups (WGs): stroke services, stroke training/capacity building, research and stroke advocacy, each with defined terms of reference. These groups generated 20 priorities (five per thematic area) during breakout sessions at the first ASLS which were further refined into four topmost priorities (one per thematic area) at the general consensus session.ResultsThe topmost priorities included promoting the development of acute stroke services (stroke services), strengthening population-based stroke education focusing on prevention and symptom recognition (stroke training), research on hypertension control to reduce stroke risk (stroke research), and developing national stroke action plans (advocacy).ConclusionSustained reduction of stroke burden in Africa requires the adaptation of best practices to the African context, building the capacity of African stroke care professionals and using available resources with political support. Improving stroke literacy in African communities is a complementary strategy to reinforce healthy lifestyle choices and improve screening and detection of hypertension and other modifiable stroke risk factors. This process will culminate in a strategic African Stroke Action Plan (ASAP), the blueprint for the control of stroke in Africa.